2011
DOI: 10.1111/j.1365-2265.2011.04161.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple forms of hypogonadism of central, peripheral or combined origin in males with Prader–Willi syndrome

Abstract: PWS patients display heterogeneity of hypogonadism: (i) hypogonadotropic hypogonadism of central origin for LH and/or FSH; (ii) early primary testicular dysfunction (Sertoli cells damage); and (iii) a combined hypogonadism (testicular origin for FSH-inhibin B axis and central origin for LH-T axis).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 30 publications
6
51
0
Order By: Relevance
“…Patients with PWS commonly fail to complete puberty, and, as a consequence, there was no final stature loss, in spite of slight bone age advance (4). In the present case, the decision to treat with GnRHa was made because of the development of aggressive behavior but also the bone age advance.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Patients with PWS commonly fail to complete puberty, and, as a consequence, there was no final stature loss, in spite of slight bone age advance (4). In the present case, the decision to treat with GnRHa was made because of the development of aggressive behavior but also the bone age advance.…”
Section: Discussionmentioning
confidence: 74%
“…Gonadal axis function, however, is not homogeneous; normal gonadotropin response to GnRH test is quite common. but hypergonadotropic hypogonadism has also been described (4). Moreover, many children present premature adrenarche that is manifested with slightly advanced bone maturation related to obesity; usually, puberty fails to progress beyond this stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 In women, there is greater phenotypic variability in relation to ovarian function. 35 Recently Radicioni et al 36 and Gross-Tsur et al 37 confirmed the heterogeneity of the reproductive hormone profile in patients with PWS.…”
Section: Hypogonadismmentioning
confidence: 76%
“…18 The degree of hypogonadism is variable and is less severe in females than in males. 19 Males only occasionally show secondary characteristics and voice change, male body habitus, or significant facial and body hair.…”
mentioning
confidence: 99%